Preparedness prevention of Covid-19 Muhammadiyah residents in Magelang, Indonesia - Margono, Margono; Masithoh, Robiul Fitri; Priyo, Priyo (LPPM STIKES MUHAMMADIYAH GOMBONG, 2020)
Corona Virus Disease (Covid-19) is a virus that is still related to the cause of Severe Acute Respiratory Syndrome (SARS) and Middle East Respiratory Syndrome (MERS) which still has an RNA chain that mutates faster than DNA. World Health Organization (WHO) said that until July 26 2020 the number of people infected with the virus were 15,785,641 people. From the data, Indonesia ranked 24th with 97,286 positive cases and 4,714 people died. The data shows that Indonesia is higher than China as the country of origin of this virus began to be found. Indonesia implemented several policies in the fields of law, health and economics to deal with the Covid-19 outbreak. The Ministry of Health issued a regulation derived from PP21 / 20, namely Minister of Health Regulation No. 9 of 2020 concerning Large Scale Limitation Guidelines (PSBB). Muhammadiyah as a social organization through the One Muhammadiyah One Response (OMOR) program in handling coviders formed the Muhmmadiyah Covid-19 Command Center (MCCC) team to contribute to the prevention of covid-19 transmission that had been formed up to the Regional level. In addition to providing care for Covid-19 patients through Muhamamdiyah and Aisyah hospitals, MCCC also prepared the community to be prepared to face the Covid-19 pandemic. In Magelang regency, up to 27 July, PDP recorded 42 deaths, positive confirmation died 6 people and confirmed 7 people were treated. Therefore the importance of community preparedness to prevent Covid-19 transmission. Method: this research uses a quantitative approach with descriptive type. This research uses a survey method with questionnaire technique. Respondents in this study were 100 people. The results of this study indicate that residents of Muhamamdiyah in Magelang District 89% of respondents have received co-19 prevention information from MCCC, 59% showed understanding of the information provided, applying health protocols with 92% hand washing habits, doing 88% exercise, habit using masks 93 %, keep a distance of 98%, use hand sanitizer 86%, maintain a 96% sneezing ethic, able to manage stress 71%, and consume nutritious food 76%